Effects of Materialism on Brand-Related User-Generated Content and Positive WOM on Social Media. Issue 2 (May 2023) - Nguyen, Han; Martin, Brett A. S.; Kerr, Gayle
This research investigates how materialism as a personality trait can impact consumers' intention to create brand-related user-generated content (UGC) and positive WOM on Facebook. The research involved three studies. Study 1 was an online survey investigating the association between materialism and brand-related UGC and positive WOM creation on Facebook. Study 2 tested the mediating role of the perception of brand symbolism for the effect of materialism on brand-related UGC and positive WOM creation. Study 3 was an online experiment which manipulated materialism. It demonstrated that the perception of brand symbolism mediated the effect of materialism on brand-related UGC and positive WOM creation on Facebook. These findings show how materialism influences whether consumers create content about brands to express self-identity. They also show researchers and managers how to target consumers to encourage them to create brand-related UGC and positive WOM on social media. Specifically, by emphasising materialistic cues, marketers can enhance consumers' perception of brand symbolism which can motivate consumers to create brand-related UGC and positive WOM.